Caracterização da PANC Ora-pro-nóbis: composição bromatológica, atividade antioxidante e digestibilidade in vitro - Daniel, Aline de Vasconcelos (2022)
The ora-pro-nóbis, Pereskia aculeata Miller is an unconventional food plant of easy agronomic cultivation and with good resistance to lack of water, being recommended for various types of climate and soil. The objective of this work is to evaluate the chemical composition, digestibility, bioactive compounds and antioxidant activity comparing the growth phase and parts of the plant with the best application in food supplementation and to determine the decrease of the nutritional components with the planting time. The highest crude protein content is in the leaves of the adult plant, 23.25%, but the whole plant and the leaf of the young plant also had a high protein content. Higher fiber content was found in the stem, increasing according to the age of the plant. A high content of mineral matter was found where the time of planting directly influences the content of macro and microminerals, both in the leaves and in the whole young plant, which proved to be an excellent source of Fe, Mg, P, S and Zn while the K, Mn, Ca, B, and Cu are predominantly in the leaves. The plant growth phase does not reduce the content of bioactive compounds, ensuring its antioxidant capacity, FRAP 12.24 µM Trolox g-1 and ABTS 12.04 µM Trolox g-1 and protective health effects. The in vitro digestibility is 68.85%, demonstrating that this PANC can be used as a food supplement for both humans and ruminant animals.